Preparation of wood fiber-based ATRP (Atom Transfer Radical Polymerization) photoinitiator and application of pressure-sensitive adhesive
By using ligno fiber-based ester derivatives as metal-free ATRP photoinitiators, the problem of impurities introduced by metal catalysts in traditional ATRP technology is solved, and polymer preparation with high purity and performance is achieved, which is suitable for a variety of industrial applications.
Patent Information
- Application Number
- CN202410976634.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-07-21
- Publication Date
- 2025-02-21
AI Technical Summary
The metal catalysts used in existing ATRP technology may introduce impurities, limiting the purity and application range of polymers, while also having problems of toxicity, environmental impact and high cost.
Lignocellulose-based ester derivatives are used as metal-free ATRP photoinitiators, prepared by esterification reaction, combined with acrylate monomers, and polymerization is initiated by ultraviolet light to prepare solvent-free pressure-sensitive adhesives.
It improves the purity and performance of polymers, expands the use of wood fibers, meets the needs of environmental protection, solvent-free, low-cost and high-performance, and is suitable for coatings, adhesives and sealing materials.
Smart Images

Figure CN119490672A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to a wood fiber-based ATRP photoinitiator, and in particular to a wood fiber-based ATRP photoinitiator, a preparation method thereof, and application of the same in preparing a pressure-sensitive adhesive. Background Art
[0002] Atom transfer radical polymerization (ATRP) is an important polymerization technology that can synthesize functional polymers by precisely controlling the growth of polymer chains. In ATRP, initiators and catalysts work together to allow monomers to be added in sequence and extend polymer chains, controlling the molecular weight and structure of the polymer. Traditional ATRP requires metal catalysts (such as copper), but these metal catalysts may introduce impurities into the polymer, limiting some applications. Problems such as toxicity, environmental impact and high cost during its synthesis have triggered the demand for more green and sustainable alternatives. Metal-free ATRP avoids metal contamination, making the synthesized polymers purer. ATRP technology is highly controllable and flexible, and can be used to prepare polymers with various structures and properties. It is widely used in materials science, biomedicine and other fields. Its unique molecular design and synthesis method make it one of the important polymerization technologies, providing a powerful tool for customized synthesis of high-performance materials. In general, metal-free ATRP technology provides a purer, environmentally friendly and flexible option for polymer synthesis, expanding the application prospects of polymers in various fields.
[0003] As a renewable and environmentally friendly material, wood fiber has shown significant advantages in many fields. Its renewable nature comes from wood, which not only helps to reduce dependence on non-renewable resources, but also complies with the principle of sustainable development. The carbon footprint generated by the production and use stages of wood fiber products is relatively low, and its degradability helps to reduce the impact on the environment. Low cost is another advantage of wood fiber. It is often extracted from wood waste, providing various industries with more competitive production costs. The good processing properties of wood fiber make it easier to handle during the preparation process. In some fields, it is used as a filler or reinforcing material to improve the strength and wear resistance of the material. Wood fiber can be realized through a variety of technologies such as biological, physical and chemical to give it new functions. These modifications can effectively control its diffusivity, thereby improving key properties such as the mechanical properties of the material.
[0004] Chinese patent CN 105906820 B reports a preparation method and application of a modified wood fiber material. The modified wood fiber can be added to papermaking as a filler to save starch, improve the surface properties of paper, and especially significantly improve the strength of paper. Chinese patent CN 103223687 B discloses a method for acetylation modification of poplar wood fiber. The prepared acetylated wood fiber is blended with plastics such as polylactic acid or polyolefin to prepare a wood-plastic composite material with low water absorption, good dimensional stability and weather resistance. It is easy to operate, has low energy consumption, short reaction time, no pollutants, and the reaction solvent can be recycled. The above patents can improve the wear resistance and mechanical properties of composite materials, but physical composite blending has problems such as poor compatibility, unstable performance, and difficult processing and molding. It is not suitable for applications that require simple, economical and rapid preparation of materials. Compared with some chemically synthesized ATRP initiators, wood fiber-based ATRP photoinitiators have lower costs and green environmental protection. This helps to reduce metal impurities that may be introduced during the ATRP polymerization process, improve polymer purity and broaden application scenarios. The performance of ATRP polymer materials can be adjusted by adjusting the particle size and content of wood fibers. The addition of wood fibers can change the mechanical properties, surface characteristics, etc. of the material, increasing the diversity of the material. Through such a modification process, wood fibers can be transformed from simple fillers to reinforcing materials. This comprehensive improvement not only expands the use of wood fibers, but also provides a useful means for optimizing their performance in the preparation of pressure-sensitive adhesives and other fields. Therefore, it is of great significance to study the multi-dimensional modification of wood fibers, especially in the field of wood fiber-based ATRP photoinitiators, to promote the performance improvement and functional expansion of wood fibers in various industrial applications. Summary of the invention
[0005] In order to solve the deficiencies of the prior art, the object of the present invention is to provide a wood fiber-based ATRP photoinitiator and a preparation method and application thereof.
[0006] In order to achieve the above object, the present invention adopts the following technical solution:
[0007] A wood fiber-based ATRP photoinitiator is a wood fiber-based ester derivative, and the structural diagram is as follows: Figure 1 As shown;
[0008] The preparation method of the above-mentioned wood fiber-based ATRP photoinitiator comprises the following steps:
[0009] A1. Disperse the wood fiber evenly in a good solvent and treat it with ultrasonic wave.
[0010] A2. Adding a certain molar ratio of an esterification agent and a catalyst into the above-mentioned wood fiber dispersion to carry out an esterification reaction. After the reaction is completed, the wood fiber ester derivatives are obtained by precipitation, washing and drying in excess deionized water.
[0011] Furthermore, in the above step A1, the mass ratio of wood fiber to good solvent is 1:5-20; the dispersion temperature is 0-120°C;
[0012] The good solution is any one of dimethyl sulfoxide, cyclohexane, toluene, N,N-dimethylformamide, ionic liquid and low eutectic solvent, the ultrasonic power is 50-100 Hz, and the ultrasonic time is 5-20 min;
[0013] Furthermore, in the above step A2, the mass ratio of wood fiber to esterification agent is 1:1-3; the reaction temperature is 0-120°C, and the reaction time is 1-8h;
[0014] The wood fiber is any one of poplar wood fiber, pine wood fiber, fir wood fiber, locust wood fiber, and wood fiber powder;
[0015] The esterification reagent is any one of 2-bromoisobutyl bromide and 2-bromopropionyl bromide;
[0016] The catalyst is any one of potassium carbonate, sodium bicarbonate, sodium hydroxide, pyridine, triethylamine and 4-dimethylaminopyridine.
[0017] A solvent-free wood fiber-based pressure-sensitive adhesive, the preparation method comprising the following steps:
[0018] A certain amount of wood fiber-based ATRP photoinitiator and photo-auxiliary agent 10-phenyl-10H-thiophenazine (BHT) are added to the acrylic ester monomers, mixed and stirred, and ultrasonically treated to make them evenly dispersed. After nitrogen purging, ultraviolet light is used to initiate monomer polymerization. After a certain reaction time, a solvent-free wood fiber-based high molecular polymer is obtained. Methanol is used to remove the unreacted monomers, and after drying at 40-60°C, it is dissolved in a good solvent and coated with a coating machine to obtain a pressure-sensitive adhesive. The schematic diagram is as follows Figure 2 As shown;
[0019] Furthermore, the mass ratio of the acrylic acid ester monomer to the wood fiber-based ATRP photoinitiator is 100:0.1-1; the amount of BHT used is 100 μL of a 5% BHT / DMF solution;
[0020] Further, the acrylic acid ester monomer is any two or more of hydroxyethyl acrylate, hydroxypropyl acrylate, tetrahydrofuran acrylate, ethyl acrylate, dodecyl acrylate, hydroxyethyl methacrylate, methyl methacrylate, lauryl acrylate, isobornyl acrylate, and glycidyl methacrylate;
[0021] Furthermore, the illumination intensity of the ultraviolet polymerization in the step is 50 to 100 mW cm -2 The light reaction time is 4 to 8 hours.
[0022] Furthermore, the redispersed good solvent is dichloromethane, and the thickness of the pressure-sensitive adhesive prepared by the coating machine is 50 to 200 μm.
[0023] The present invention is beneficial in that:
[0024] The present invention provides an esterified wood fiber material, which has good dispersibility in conventional solvents and acrylic ester monomers. By adjusting the particle size and content of the wood fiber, the performance of the photocurable material can be adjusted, the use of the wood fiber can be expanded, and a beneficial means is provided for optimizing its performance in the fields of pressure-sensitive adhesive preparation and the like.
[0025] Esterified wood fiber materials are used as initiators, with advantages such as high initiation efficiency and no by-products. They are used to prepare pressure-sensitive adhesives to meet the requirements of environmental protection, solvent-free, low cost, and high performance. At the same time, the wood fiber-based ATRP photoinitiator used has the advantages of being green and renewable, which meets the needs of modern society for sustainable development.
[0026] A solvent-free pressure-sensitive adhesive was prepared using a wood fiber-based ATRP photoinitiator. It combines the viscoelastic properties of acrylic acid esters. The pressure-sensitive adhesive has been optimized in terms of sustained adhesion, initial adhesion and 180° peeling, showing better mechanical properties and enhancing its durability and adaptability in actual use. The characteristics of this pressure-sensitive adhesive are consistent with the current market demand for environmental protection, solvent-free, low-cost, high strength and renewable, and is expected to be widely used in coatings, adhesives, sealing materials and other fields. BRIEF DESCRIPTION OF THE DRAWINGS
[0027] Figure 1 Schematic diagram of the structure of wood fiber-based ester derivatives.
[0028] Figure 2 Schematic diagram of the structure of wood fiber-based pressure-sensitive adhesive.
[0029] Figure 3 This is the infrared spectra of wood fiber and 2-bromoisobutyryl bromide esterified wood fiber.
[0030] Figure 4 These are the microscope photos and infrared spectra of the 2-bromoisobutyryl bromide esterified wood fiber system before and after ATRP polymerization.
[0031] Figure 5Comparison of initial adhesion of pressure-sensitive adhesives prepared by ATRP polymerization of 2-bromoisobutyryl bromide-esterified wood fibers with different lauryl methacrylates (MMA) and isobornyl acrylate (IBOA).
[0032] Figure 6 This is a comparison chart of the 180° peel force of pressure-sensitive adhesives prepared by ATRP polymerization of 2-bromoisobutyryl bromide-esterified wood fibers with different lauryl methacrylates (MMA) and isobornyl acrylate (IBOA).
[0033] Figure 7 This is a comparison chart of the adhesion strength of pressure-sensitive adhesives prepared by ATRP polymerization of 2-bromoisobutyryl bromide-esterified wood fibers with different lauryl methacrylates (MMA) and isobornyl acrylate (IBOA).
[0034] Figure 8 This is a comparison chart of the adhesion strength of pressure-sensitive adhesives prepared by ATRP polymerization of wood fibers esterified with different contents of 2-bromoisobutyryl bromide and lauryl methacrylate (MMA) and isobornyl acrylate (IBOA). DETAILED DESCRIPTION
[0035] The present invention is described in detail below with reference to the accompanying drawings and specific embodiments.
[0036] The reagents used in this example are all commercially available.
[0037] The instruments and testing methods used in the test are:
[0038] Infrared equipment: Nicolet iS10 Fourier transform infrared spectrometer (FT-IR), Thermo Fisher Scientific;
[0039] Photopolymerization equipment: 12V3528 UV circular ring light strip, Shenzhen Jincheng Lighting Co., Ltd.;
[0040] Coating equipment: KJ-6017B vacuum adsorption coating machine, Guangdong Kejian Instrument Co., Ltd.;
[0041] Microscope: DMM-880C projection-type transflective metallographic microscope, Shanghai Caikang Optical Instrument Co., Ltd.
[0042] Initial adhesion test equipment: LT-3000 ring initial adhesion tester, Jinan Sanquan Zhongshi Experimental Instrument Co., Ltd.;
[0043] Adhesion test equipment: CZY-6S adhesion tester, Jinan Languang Electromechanical Technology Co., Ltd.
[0044] 180° peel test equipment, INSTRON 4466 universal tensile testing machine, Shenzhen Meister Co., Ltd., China.
[0045] A wood fiber-based ATRP photoinitiator is a wood fiber-based ester derivative, characterized in that the structural schematic diagram is as shown in Figure 1 As shown;
[0046] The preparation method of the above-mentioned wood fiber-based ATRP photoinitiator comprises the following steps:
[0047] A1. Disperse the wood fiber evenly in a good solvent and treat it with ultrasonic wave.
[0048] A2. Adding a certain molar ratio of an esterification agent and a catalyst into the above-mentioned wood fiber dispersion to carry out an esterification reaction. After the reaction is completed, the wood fiber ester derivatives are obtained by precipitation, washing and drying in excess deionized water.
[0049] In the above step A2, the mass ratio of wood fiber to esterification reagent is 1:1-3; the reaction temperature is 0-120°C, and the reaction time is 1-8h;
[0050] The wood fiber is any one of poplar wood fiber, pine wood fiber, fir wood fiber, locust wood fiber, and wood fiber powder;
[0051] The esterification reagent is any one of 2-bromoisobutyl bromide and 2-bromopropionyl bromide;
[0052] The catalyst is any one of potassium carbonate, sodium bicarbonate, sodium hydroxide, pyridine, triethylamine, and 4-dimethylaminopyridine;
[0053] The good solution is any one of dimethyl sulfoxide, cyclohexane, toluene, N,N-dimethylformamide, ionic liquid and low eutectic solvent. The ultrasonic power is 50-100 Hz, and the ultrasonic time is 5-20 min.
[0054] A method for preparing a wood fiber-based ATRP photoinitiator in a solvent-free pressure-sensitive adhesive comprises the following steps:
[0055] A certain mass of wood fiber-based ATRP photoinitiator and photo-auxiliary agent are added to the acrylate monomer, mixed and stirred, ultrasonically treated to make it evenly dispersed, purged with nitrogen, and then irradiated with ultraviolet light to initiate monomer polymerization. After a certain reaction time, a solvent-free wood fiber-based high molecular polymer is obtained. Unreacted monomers are removed with methanol, dried at 40-60°C and then dissolved in a good solvent, and coated with a coating machine to obtain a pressure-sensitive adhesive. The mass ratio of acrylate derivative monomers and wood fiber-based ATRP photoinitiator is 100:0.1-1, the amount of photo-auxiliary agent BHT is 100 μL, and the acrylate monomer is any two or more of hydroxyethyl acrylate, hydroxypropyl acrylate, tetrahydrofuran acrylate, ethyl acrylate, dodecyl acrylate, hydroxyethyl methacrylate, methyl methacrylate, lauryl acrylate, isobornyl acrylate, and glycidyl methacrylate. The illumination intensity of ultraviolet polymerization is 50-100 mW cm -2 , the light reaction time is 4 to 8 hours, the good solvent for redispersion is dichloromethane, and the thickness of the pressure-sensitive adhesive prepared by the coating machine is 50 to 200 μm.
[0056] Example 1
[0057] Preparation of wood fiber based photoinitiator:
[0058] Take 1g of poplar wood fiber, add it to 10g of ionic liquid, add 5mL of 2-bromoisobutyryl bromide and 0.2g of 4-dimethylaminopyridine, stir vigorously to make it dispersed evenly, and react the mixed solution at room temperature for 6h. After the reaction, the product is precipitated in excess deionized water, and then washed and filtered to prepare 2-bromoisobutyryl bromide esterified wood fiber under vacuum drying conditions, which is used as a wood fiber-based ATRP photoinitiator for standby use.
[0059] Among them, the infrared spectra of wood fiber and 2-bromoisobutyryl bromide esterified wood fiber are as follows: Figure 3 As shown in Figure 2, the vibration absorption peak of the hydroxyl group (-OH) of wood fiber is at 3350 cm -1 After esterification with acryloyl chloride, the hydroxyl (-OH) vibration absorption peak of 2-bromoisobutyryl bromide esterified wood fiber is at 3340 cm -1 Lowered, at 1720cm -1 The strong vibration absorption peak of the ester bond (C=O) appears, indicating that the esterification reaction of the wood fiber is successful, thereby judging the successful synthesis of 2-bromoisobutyryl bromide esterified wood fiber.
[0060] Preparation of UV photopolymerized solvent-free wood fiber-based pressure-sensitive adhesive:
[0061] Taking isobornyl acrylate monomer and lauryl methacrylate monomer as an example, 4 g of lauryl methacrylate (MMA) and 2 g of isobornyl acrylate (IBOA) were mixed with 20 mg of ATRP photoinitiator (2-bromoisobutyryl bromide esterified wood fiber) and 100 μL of BHT, ultrasonicated at 70 Hz for 10 min, uniformly dispersed in a 25 mL single-mouth bottle, and 5 mL of DMF was added as a diluent. After nitrogen purging for 20 min, the light intensity was 50 mW / cm -2 The monomers were polymerized by UV light irradiation for 6 hours to obtain wood fiber-based polymers. Unreacted monomers were removed by methanol, and the polymers were dried at 40-60°C and dissolved in dichloromethane. The polymers were coated by a coating machine and dried to obtain a pressure-sensitive adhesive with a thickness of 100 μm.
[0062] In Example 1, the optical microscopic image of the polyacrylate pressure-sensitive adhesive prepared by using 2-bromoisobutyryl bromide esterified wood fiber as an ATRP photoinitiator is as follows: Figure 4 As shown in a, the microstructure of the modified wood fiber can be clearly seen before polymerization, and after photopolymerization, the 2-bromoisobutyryl bromide esterified wood fiber and the acrylate monomer form a cross-linked polymerization network, and the surface morphology is smoother, but the network of the modified wood fiber can still be observed. Figure 4 b shows 1627cm -1 The C=C double bond stretching vibration peak decreases sharply, while the 2850-2950cm -1 The methyl peak and methylene peak increased significantly, indicating that 2-bromoisobutyryl bromide esterified wood fiber successfully initiated the polymerization of acrylate monomers as ATRP photoinitiator.
[0063] Example 2
[0064] As shown in Example 1, the difference is that the molar mass ratio of the two acrylate monomers is different.
[0065] Taking isobornyl acrylate monomer and lauryl methacrylate monomer as an example, 4 g of lauryl methacrylate (MMA) and 1.4 g of isobornyl acrylate (IBOA) were mixed with 20 mg of ATRP photoinitiator (2-bromoisobutyryl bromide esterified wood fiber) and 100 μL of BHT, ultrasonicated at 70 Hz for 10 min, uniformly dispersed in a 25 mL single-mouth bottle, and 5 mL of DMF was added as a diluent. After nitrogen purging for 20 min, the light intensity was 50 mW / cm -2 The monomers were polymerized by UV light irradiation for 6 hours to obtain wood fiber-based polymers. Unreacted monomers were removed by methanol, and the polymers were dried at 40-60°C and dissolved in dichloromethane. The polymers were coated by a coating machine and dried to obtain a pressure-sensitive adhesive with a thickness of 100 μm.
[0066] In Example 2, the performance of the polyacrylate pressure-sensitive adhesive prepared by using 2-bromoisobutyryl bromide esterified wood fiber as a photoinitiator can be obtained from Figure 5 , Figure 6 , Figure 7 As can be seen from the figure, the initial adhesion of the pressure-sensitive adhesive prepared by using 2-bromoisobutyryl bromide esterified wood fiber as ATRP photoinitiator is 25.92N, the 180° peel strength is 17.45N·25mm, and the adhesion time is 0.09h.
[0067] Example 3
[0068] As shown in Example 1, the difference is that the molar mass ratio of the two acrylate monomers is different.
[0069] Taking isobornyl acrylate monomer and lauryl methacrylate monomer as an example, 4.5 g of lauryl methacrylate (MMA) and 0.92 g of isobornyl acrylate (IBOA) were mixed with 20 mg of ATRP photoinitiator (2-bromoisobutyryl bromide esterified wood fiber) and 100 μL of BHT, ultrasonicated at 70 Hz for 10 min, uniformly dispersed in a 25 mL single-mouth bottle, and 5 mL of DMF was added as a diluent. After nitrogen purging for 20 min, the light intensity was 50 mW / cm -2 The monomers were polymerized by UV light irradiation for 6 hours to obtain wood fiber-based polymers. Unreacted monomers were removed by methanol, and the polymers were dried at 40-60°C and dissolved in dichloromethane. The polymers were coated by a coating machine and dried to obtain a pressure-sensitive adhesive with a thickness of 100 μm.
[0070] In Example 3, the performance of the polyacrylate pressure-sensitive adhesive prepared by using 2-bromoisobutyryl bromide esterified wood fiber as a photoinitiator can be seen from Figure 5 , Figure 6 , Figure 7 As can be seen from the figure, the initial adhesion of the pressure-sensitive adhesive prepared by using 2-bromoisobutyryl bromide esterified wood fiber as ATRP photoinitiator is 15.58N, the 180° peel strength is 19.91N·25mm, and the adhesion time is 0.42h.
[0071] Example 4
[0072] As shown in Example 1, the difference is that the molar mass ratio of the two acrylate monomers is different.
[0073] Taking isobornyl acrylate monomer and lauryl methacrylate monomer as an example, 3.5 g of lauryl methacrylate (MMA) and 1.91 g of isobornyl acrylate (IBOA) were mixed with 20 mg of ATRP photoinitiator (2-bromoisobutyryl bromide esterified wood fiber) and 100 μL of BHT, ultrasonicated at 70 Hz for 10 min, uniformly dispersed in a 25 mL single-mouth bottle, and 5 mL of DMF was added as a diluent. After nitrogen purging for 20 min, the light intensity was 50 mW / cm -2 The monomers were polymerized by UV light irradiation for 6 hours to obtain wood fiber-based polymers. Unreacted monomers were removed by methanol, and the polymers were dried at 40-60°C and dissolved in dichloromethane. The polymers were coated by a coating machine and dried to obtain a pressure-sensitive adhesive with a thickness of 100 μm.
[0074] In Example 4, the performance of the polyacrylate pressure-sensitive adhesive prepared by using 2-bromoisobutyryl bromide esterified wood fiber as a photoinitiator can be seen from Figure 5 , Figure 6 , Figure 7 As can be seen from the figure, the initial adhesion of the pressure-sensitive adhesive prepared by using 2-bromoisobutyryl bromide esterified wood fiber as ATRP photoinitiator is 14.6N, the 180° peel strength is 25.37N·25mm, and the adhesion time is 2.99h.
[0075] Example 5
[0076] As shown in Example 1, the difference is that the molar mass ratio of the two acrylate monomers is different.
[0077] Taking isobornyl acrylate monomer and lauryl methacrylate monomer as an example, 3 g of lauryl methacrylate (MMA) and 2.45 g of isobornyl acrylate (IBOA) were mixed with 20 mg of ATRP photoinitiator (2-bromoisobutyryl bromide esterified wood fiber) and 100 μL of BHT, ultrasonicated at 70 Hz for 10 min, uniformly dispersed in a 25 mL single-mouth bottle, and 5 mL of DMF was added as a diluent. After nitrogen purging for 20 min, the light intensity was 50 mW / cm -2 The monomers were polymerized by UV light irradiation for 6 hours to obtain wood fiber-based polymers. Unreacted monomers were removed by methanol, and the polymers were dried at 40-60°C and dissolved in dichloromethane. The polymers were coated by a coating machine and dried to obtain a pressure-sensitive adhesive with a thickness of 100 μm.
[0078] In Example 5, the performance of the polyacrylate pressure-sensitive adhesive prepared by using 2-bromoisobutyryl bromide esterified wood fiber as a photoinitiator can be seen from Figure 5 , Figure 6 , Figure 7As can be seen from the figure, the initial adhesion of the pressure-sensitive adhesive prepared by using 2-bromoisobutyryl bromide esterified wood fiber as ATRP photoinitiator is 12.26N, the 180° peel strength is 28.49N·25mm, and the adhesion time is 6.85h.
[0079] Example 6
[0080] As shown in Example 1, the difference is that the amount of ATRP photoinitiator used and the molar mass ratio of the two acrylate monomers are different.
[0081] Taking isobornyl acrylate monomer and lauryl methacrylate monomer as examples, 3 g of lauryl methacrylate (MMA) and 2.45 g of isobornyl acrylate (IBOA) were mixed with 10 mg, 20 mg, and 30 mg of ATRP photoinitiator (2-bromoisobutyryl bromide esterified wood fiber) and 100 μL of BHT, respectively, and ultrasonicated for 10 min at 70 Hz. The mixture was evenly dispersed in a 25 mL single-mouth bottle, and 5 mL of DMF was added as a diluent. After nitrogen purging for 20 min, the mixture was subjected to a light intensity of 50 mW / cm -2 The monomers were polymerized by UV light irradiation for 6 hours to obtain wood fiber-based polymers. Unreacted monomers were removed by methanol, and the polymers were dried at 40-60°C and dissolved in dichloromethane. The polymers were coated by a coating machine and dried to obtain a pressure-sensitive adhesive with a thickness of 100 μm.
[0082] In Example 6, the properties of the polyacrylate pressure-sensitive adhesive prepared by using different amounts of 2-bromoisobutyryl bromide esterified wood fiber as a photoinitiator can be seen from Figure 8 As can be seen from the figure, the pressure-sensitive adhesive prepared using 10 mg, 20 mg, and 30 mg of 2-bromoisobutyryl bromide esterified wood fiber as ATRP photoinitiator has a tack-retaining time of 4 h, 7.07 h, and 5.85 h, respectively.
[0083] The above shows and describes the basic principles, main features and advantages of the present invention. Those skilled in the art should understand that the above embodiments do not limit the present invention in any form, and any technical solution obtained by equivalent replacement or equivalent transformation falls within the protection scope of the present invention.
Claims
1. A wood fiber-based ATRP photoinitiator, which is a wood fiber-based ester derivative.
2. The method for preparing a wood fiber-based ATRP photoinitiator according to claim 1, characterized in that: The preparation method comprises the following steps: A1. Disperse the wood fiber evenly in a good solvent and treat it with ultrasonic wave. A2. Adding a certain molar ratio of an esterification agent and a catalyst into the above-mentioned wood fiber dispersion to carry out an esterification reaction. After the reaction is completed, the wood fiber ester derivatives are obtained by precipitation, washing and drying in excess deionized water. The method for preparing a wood fiber-based ATRP photoinitiator according to claim 2, characterized in that the good solution in step A1 is any one of dimethyl sulfoxide, cyclohexane, toluene, N,N-dimethylformamide, ionic liquid and low eutectic solvent; the ultrasonic power is 50 to 100 Hz; the ultrasonic time is 5 to 20 min; In step A2, the mass ratio of wood fiber to esterification agent is 1:1-3; the reaction temperature is 0-120°C, and the reaction time is 1-8h; The wood fiber is any one of poplar wood fiber, pine wood fiber, fir wood fiber, locust wood fiber, and wood fiber powder; The esterification reagent is any one of 2-bromoisobutyl bromide and 2-bromopropionyl bromide.
3. Use of the wood fiber-based ATRP photoinitiator as claimed in claim 1 in a solvent-free pressure-sensitive adhesive.
4. The use according to claim 4, characterized in that: The solvent-free pressure-sensitive adhesive comprises: a wood fiber-based ATRP photoinitiator and an acrylate derivative monomer, wherein the mass ratio of the acrylate derivative monomer to the wood fiber-based ATRP photoinitiator is 100:0.1-1.
5. A method for preparing a solvent-free wood fiber-based pressure-sensitive adhesive, characterized in that: The following steps are involved: B1. Prepare a wood fiber-based ATRP photoinitiator using the method of claim 2; B2. Add a certain amount of wood fiber-based ATRP photoinitiator and photo-auxiliary agent 10-phenyl-10H-thiophenazine (BHT) to the acrylic ester monomer, mix and stir, and disperse it evenly by ultrasonic treatment. After nitrogen purging, use ultraviolet light to initiate monomer polymerization. After a certain reaction time, a solvent-free wood fiber-based high molecular polymer is obtained. Use methanol to remove the unreacted monomer, dry it at 40-60°C, and then dissolve it in a good solvent, and use a coating machine to coat it to obtain a pressure-sensitive adhesive.
6. The method for preparing the solvent-free wood fiber-based pressure-sensitive adhesive according to claim 6, characterized in that: In the step B2, the mass ratio of the acrylic acid ester monomer to the wood fiber-based ATRP photoinitiator is 100:0.1-1; the amount of BHT used is 100 μL of a 5% BHT / DMF solution; The acrylic acid ester monomers are any two or more of hydroxyethyl acrylate, hydroxypropyl acrylate, tetrahydrofuran acrylate, ethyl acrylate, lauryl acrylate, hydroxyethyl methacrylate, methyl methacrylate, lauryl acrylate, isobornyl acrylate and glycidyl methacrylate.
7. The method for preparing the solvent-free wood fiber-based pressure-sensitive adhesive according to claim 7, characterized in that: The illumination intensity of the ultraviolet polymerization in the step is 50-100 mW cm -2 , the light reaction time is 4 to 8 hours, the good solvent for redispersion is dichloromethane, and the thickness of the pressure-sensitive adhesive prepared by the coating machine is 50 to 200 μm.
Citation Information
Patent Citations
A method for acetylation modification of poplar wood powder
CN103223687B
A modified wood flour material, its preparation method and application
CN105906820B